Acute and chronic stress in daily police service: a three-week N-of-1 study - Voigt, Laura; Oudejans, Raôul R. D.; Hutter, Vana; Plessner, Henning; Strahler, Jana; Frenkel, Marie Ottilie (Psychoneuroendocrinology, 2020)
On duty, police officers are exposed to a variety of acute, threatening stress situations and organizational demands. In line with the allostatic load model, the resulting acute and chronic stress might have tremendous consequences for police officers’ work performance and psychological and physical health. To date, limited research has been conducted into the underlying biological, dynamic mechanisms of stress in police service. Therefore, this ecological momentary assessment study examined the associations of stress, mood and biological stress markers of a 28-year-old male police officer in a N-of-1 study over three weeks (90 data points). Four times a day (directly after waking up, 30 minutes later, 6 hours later, before going to bed), he answered questions about the perceived stress and mood using a smartphone application. With each data entry, he collected saliva samples for the later assessment of salivary cortisol (sCort) and alpha-amylase (sAA). In addition, data was collected after six police incidents during duty. sCort and sAA were not related to perceived stress in daily life and did not increase in police incidents. Regarding mood measures, deterioration of calmness, but not valence and energy was associated with perceived stress. The results suggest continued police service to constitute a major chronic stressor resulting in an inability to mount a proper response to further acute stress. As an indicator of allostatic load, psychological and biological hyporesponsivity in moments of stress may have negative consequences for police officers’ health and behavior in critical situations that require optimal performance. Prospectively, this research design may also become relevant when evaluating the efficacy of individualized stress management interventions in police training.